Effects of Mercury on Growth, Emergence, and Behavior of Chironomus riparius Meigen (Diptera: Chironomidae) - Azevedo-Pereira, HMVS
Mercury is a pervasive toxicant that can be found in the environment due to anthropogenic activity as well as natural sources. The majority of studies in freshwater environments focus mainly on bioaccumulation, population dynamics, and biomagnification. Here, we study the effects of mercuric chloride on Chironomus riparius Meigen, simulating a mercury discharge on a freshwater ecosystem. Growth, emergence, development time, and behavior were the end points assessed. Growth was measured after 8 days of exposure and behavior was recorded on days 4 and 10 of the experimental period. The behavioral responses of C. riparius to different mercury treatments were recorded with an online biomonitor, which allows a more objective and precise behavioral understanding than visual observation. Mercury exposure resulted in reductions in growth and emergence, a delayed development time, and a decrease in locomotor activity of the larvae. Our results demonstrate that mercury exposure can impair life-history responses of chironomids.